A pilot multiple crossover, randomized controlled trial of methylphenidate in mild cognitive impairment using standardized tests and daily brain games to track cognition: Neuropsychiatry and behavioral neurology/treatment development and clinical trials. (7th December 2020) - DesRuisseaux, Libby A.; Williams, Victoria J.; McManus, Alison J.; Gupta, Anoopum S.; Bolling, Anna M.; Schwab, Nadine A.; Riley, Misha M.; Carlyle, Becky C.; Azami, Hamed; Gerber, Jessica A.; Betensky, Rebecca A.; Arnold, Steven E.
Abstract: Background: Conventional clinical trial design in AD and AD‐related disorders (ADRD) is the parallel‐group randomized controlled trial. However this design requires large sample sizes to detect meaningful effects in an "average" patient. They are costly, and have not yielded new treatments for many years. As an alternative, the multi‐crossover, randomized control trial (MCRCT) is a design in which patients serve as their own control across successive, randomized blocks of active treatment and placebo. This design overcomes many limitations of a parallel group trial, yielding unbiased assessment of individual treatment effects ("N‐of‐1") regardless of unique patient characteristics. The goal of this study is to pilot a MCRCT of a potential symptomatic treatment, methylphenidate, for mild‐stage AD/ADRDs, testing feasibility and compliance of participants in this design and efficacy of the drug using standard and novel outcome measures suited for this design. Methods: Ten participants with mild cognitive impairment or mild‐stage dementia due to AD/ADRDs will undergo a four‐week lead‐in period followed by three, month‐long treatment blocks (two weeks of treatment with methylphenidate, two weeks placebo in random order). The primary outcome of interest is cognition, measured using standard office‐based assessments at the end of each treatment period and daily home‐based brain games played throughout the study. Secondary and exploratory outcomes include neuropsychiatric and functional assessments, actigraphy, and other novel digital cognitive and neurophysiological assessments. Result: Currently, five participants (three male, mean age = 65.6, mean education = 17.6 years, mean MoCA = 23/30) have been screened and randomized. Preliminary interim analyses are ongoing. Conclusion: This pilot study will gauge feasibility of conducting a MCRCT trial for symptomatic treatment in early AD/ADRDs, compare home‐based daily brain games with standard office‐based cognitive measures, and explore practicability and potential utility of novel digital phenotyping tools within a clinical trial for AD/ADRD. Particular attention will be paid to compliance, tolerability of drug and participation, learning effects, trends and stability of daily measures across blocks, medication carryover effects, and correlations between home and office‐based assessments. These data will provide guidance for more efficient trial design and use of potentially more robust, ecological outcome measures in AD/ADRD research.